Students Perceptions of the Benefits and Challenges of Using ChatGPT for English Speaking: A Systematic Review - Karolina Okwin Hitokdana (Hasanuddin University, 2025)
The rise of ChatGPT as a tool in language learning has created new opportunities, particularly in the English as a Foreign Language (EFL) context, for enhancing students' speaking skills. Therefore, it is important to explore EFL students’ perspectives on the benefits and challenges of using ChatGPT to learn English speaking skills. To achieve the objectives of this research, the researcher used the systematic review method by reviewing 20 empirical articles published between 2023 and 2025, using Google Scholar. The findings of the analysis were classified into five main themes. The first three themes were related to the benefits of using ChatGPT to learn speaking: (1) ChatGPT might reduce students’ anxiety, (2) ChatGPT might enhance students’ motivation, (3) ChatGPT might enhance students’ learning flexibility. Meanwhile, the other themes were related to the challenges of using ChatGPT: (4) ChatGPT may not give students authentic interaction as a human, and (5) ChatGPT poses a risk of student over-reliance. Each theme is discussed and connected to the relevant literature, accompanied by practical solutions and recommendations for future research.